The Effect of Motivation and Work Experience on Career Development in Employees of the PPIC Department of PT. Shoetown Ligung Indonesia - Masduki Masduki; Lalu Suparto; Wisnu Tris Ferdiansyah (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
In a company, human resources or employees are the most important asset for achieving common goals. A company can develop quickly depending on the workers in it, therefore if the company wants good changes and progress in achieving its goals, then the employees who are hired must also have good abilities. The research method used is a survey method with a descriptive and verification approach. The population in this study were employees of the PPIC department of PT. Shoetown Ligung Indonesia, totaling 305 people. Determination of the sample in this study using Probability Sampling with Simple Random Sampling technique. The measurement scale in this study uses a Likert scale. Analysis of the data used in this study is multiple linear regression analysis and analysis of the coefficient of determination, which first performed the classical assumption test, then tested the hypothesis. The results of this study indicate that partially motivational variables have a positive and significant influence on career development. Partially, the work experience variable has a positive and significant influence on career development. Simultaneously variables of motivation and work experience have a positive and significant influence on career development.